Alternative financing mechanisms for ART programs in health facilities in Uganda: a mixed-methods approach - Zakumumpa, Henry; Bennett, Sara; Ssengooba, Freddie (BMC health services research, 2017)
Sub-Saharan Africa is heavily dependent on global health initiatives (GHIs) for funding antiretroviral therapy (ART) scale-up. There are indications that global investments for ART scale-up are flattening. It is unclear what new funding channels can bridge the funding gap for ART service delivery. Many previous studies have focused on domestic government spending and international funding especially from GHIs. The objective of this study was to identify the funding strategies adopted by health facilities in Uganda to sustain ART programs between 2004 and 2014 and to explore variations in financing mechanisms by ownership of health facility. Methods: A mixed-methods approach was employed. A survey of health facilities (N = 195) across Uganda which commenced ART delivery between 2004 and 2009 was conducted. Six health facilities were purposively selected for in-depth examination. Semi-structured interviews (N = 18) were conducted with ART Clinic managers (three from each of the six health facilities). Statistical analyses were performed in STATA (Version 12.0) and qualitative data were analyzed by coding and thematic analysis. Results: Multiple funding sources for ART programs were common with 140 (72%) of the health facilities indicating at least two concurrent grants supporting ART service delivery between 2009 and 2014. Private philanthropic aid emerged as an important source of supplemental funding for ART service delivery. ART financing strategies were differentiated by ownership of health facility. Private not-for-profit providers were more externally-focused (multiple grants, philanthropic aid). For-profit providers were more client-oriented (fee-for-service, insurance schemes). Public facilities sought additional funding streams not dissimilar to other health facility ownership-types.
Keywords: ART scale-up; HIV funding; Health systems; Implementation research